The strength and persistence of entrepreneurial cultures - James Foreman-Peck; Peng Zhou (Cardiff University, Cardiff Business School, 2010)
The twentieth century United States provides a natural experiment to measure the strength and persistence of entrepreneurial cultures. Assuming immigrants bear the cultures of their birth place, comparison of revealed entrepreneurial propensities of US immigrant groups in 1910 and 2000 reflected these backgrounds. According to this test North-western Europe, where modern economic growth is widely held to have originated, did not host unusually strong entrepreneurial cultures. Instead such cultures were carried by persons originating from Greece, Turkey and Italy, together with Jews. The rise of widespread female entrepreneurship provides additional evidence by showing that this trait systematically responded less strongly, but in the same way, to cultural background as did male entrepreneurship.
Keywords: D01; J15; J23; J61; 330; Entrepreneurship; Culture; Migration; Entrepreneurship-Ansatz; Persönlichkeitspsychologie; Kulturelle Identität; Einwanderung; Religion; Nordeuropa; Südeuropa; USA